2019
DOI: 10.1159/000503560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Nursing In-Service Education Program on Nurses’ Knowledge and Attitudes towards Pain Management in a Governmental Hospital in the United Arab Emirates: Experimental Random Assignment Study

Abstract: <b><i>Background:</i></b> Pain is the most common symptom, which is often experienced in acute illnesses and is one of the symptoms that patients feel apprehensive about. Undertaking pain management aims to prevent negative physiological and psychological outcomes. Inadequate knowledge about pain and its characteristics is a common barrier to effective pain management. Evidence shows that if nurses have adequate knowledge and a positive attitude towards pain, it may lead to more effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The in-service education pain management programme therefore proved to be effective. [20] This present study also revealed that there was a relationship between the teaching programme and the knowledge of route and other skills required for the administration of postoperative pain drugs. This substantiates a study [21] carried out on 150 undergraduate medical students of Gandhi Medical College, India, for a period of 3 months, which found that of 136 students, 93.4% had seen intramuscular (IM) or intravenous (IV)…”
Section: Discussionsupporting
confidence: 63%
“…The in-service education pain management programme therefore proved to be effective. [20] This present study also revealed that there was a relationship between the teaching programme and the knowledge of route and other skills required for the administration of postoperative pain drugs. This substantiates a study [21] carried out on 150 undergraduate medical students of Gandhi Medical College, India, for a period of 3 months, which found that of 136 students, 93.4% had seen intramuscular (IM) or intravenous (IV)…”
Section: Discussionsupporting
confidence: 63%
“…Domenech et al (2011) 18 also used the FABQ. This enabled a sensitivity analyses x Maclaren et al 49 x Zhang et al 76 x Dwyer et al 21 x El-Aqoul et al 22 x Salim et al 63 x Yoo et al 75 x Johnston et al 41 x…”
Section: Attitudesmentioning
confidence: 99%
“…Results showed that the mean K&A score increased after the pain education program from 61.36 (SD 11.60) to 69.94 (SD 7.74), while in the control group, the mean K&A score slightly decreased in the post-test (mean ± SD, 60.99 ± 11.53%) comparing to the pre-test (mean ± SD, 61.00 ± 11.60%), though this small mean decrease of 0.01 was not statistically significant (t(99)=1.41, P>0.05). The study concluded that nurses who received the education program improved their level of K&A compared to the control group who did not receive any educational programs (Salim, Joshua, AbuBaker, Chehab, & Jose, 2019).…”
Section: Nurses' Knowledge and Attitudes About Pain Assessment And Ma...mentioning
confidence: 94%
“…A recent study by Salim et al (2019) assessed the effect of delivering a nursingspecific educational program regarding pain management in a governmental hospital in Dubai, United Arab Emirates. The experimental study used a random assignment design with a pre-test/post-test and was conducted over a two-month period between February and April 2019.…”
Section: Nurses' Knowledge and Attitudes About Pain Assessment And Ma...mentioning
confidence: 99%